Supplementary Feeding Program Evaluation Restoration Malnourished In Children Under Five In The District Wonogiri Seen From Input and Process Aspects - Ratna Indriati; Sri Achadi Nugraheni; Apoina Kartini (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2015)
Salah satu upaya untuk mengatasi masalah kurang gizi di Kabupaten Wonogiri adalah dengan program PMT-P. Program ini sudah dilakukan sejak tahun 2007 namun belum menunjukkan hasil yang bermakna. Hasil studi pendahuluan menunjukkan masih ada kendala dalam aspek input dan proses dalam pelaksanaan program ini. Tujuan penelitian untuk mengevaluasi pelaksanaan program PMT-P balita kurang gizi. Jenis penelitian observasional analitik dengan metode kualitatif untuk mengevaluasi pelaksanaan program PMT-P oleh TPG dan kuantitatif untuk membandingkan pelaksanaan program PMT-P oleh bidan desa antara puskesmas yang mengalami peningkatan dan penurunan kasus balita kurang gizi. Informan utama 4 TPG dari 4 puskesmas yang mengalami peningkatan dan penurunan kasus balita kurang gizi. Informan triangulasi yaitu 4 kepala puskesmas, Kasi Kesga dan Gizi DKK, 4 bidan desa, 4 kader posyandu, dan ibu balita penerima PMT-P. Subjek penelitian kuantitatif adalah 60 bidan desa yang dipilih secara purposif dari puskesmas tersebut. Pengumpulan data kualitatif melalui wawancara mendalam dan kuantitatif dengan angket. Analisis data kualitatif dengan contentanalysis dan kuantitatif dengan uji statistik Mann Whitney. Pelaksanaan PMT-P di puskesmas yang mengalami penurunan kasus kurang gizi lebih banyak yang optimal (83,3%) dibandingkan puskesmas yang mengalami peningkatan kasus (56,7%). Perbedaan mencolok pada pelaksanaan meliputi sosialisasi ke masyarakat, registrasi sasaran, pemantauan daya terima makanan tambahan, penggunaan kartu pemantauan serta pendampingan bidan terhadap kader lebih banyak dilakukan oleh puskesmas yang mengalami penurunan kasus balita kurang gizi. Pemberian paket PMT-P di puskesmas yang mengalami peningkatan kasus dilakukan pada semua balita dengan rata-rata pemberian selama satu bulan. Selain itu puskesmas kurang melibatkan perangkat desa dan kecamatan dalam PMT-P. Penentuan sasaran dengan tepat dan peningkatan peran serta masyarakat dapat menurunkan kasus kurang gizi. One of efforts to solve undernourishment problems in Wonogiri district was a recovery food supplement distribution (PMT-P) program. This program has been implemented since 2007. However, it had not shown significant results. Preliminary studies showed that there were problems in input and process aspects in the implementation of this program. Objective of the study was to evaluate the implementation of PMT-P program for undernourished under-five children (balita). This was an observational-analytical study. A qualitative method was applied to evaluate the implementation of PMT-P program by TPG. A quantitative method was used to compare the implementation of PMT-P program by midwives in the primary healthcare centers (puskesmas) with increasing and decreasing numbers of undernourished under-five children cases. The main informants were four TPG from four puskesmas that experienced the increase and decrease numbers of undernourished under-five children cases. Triangulation informants were four heads of puskesmas, a head of Kesga and nutrition section of the district health office, four village midwives, four posyandu cadres, and mothers of under-five children who received PMT-P. Subject of the quantitative study were 60 midwives selected purposively from each puskesmas. Qualitative data were collected through in-depth interview; quantitative data were collected using questionnaire. Content analysis was applied for qualitative data analysis, and Mann-Whitney statistic test was applied for quantitative data analysis. Implementation of PMT- P in puskesmas that experienced the decrease of the number of undernourished cases was more optimal (83.3%) than in puskesmas that experienced the increase of the cases (56.7%). Distinct difference that was shown in the implementation included socialization to the community, target registration, monitoring of PMT absorption ability, monitoring card usage. Midwives accompaniment to cadres was conducted more frequent by puskesmas that experienced the decrease of the number of undernourished under-five children cases. PMT-P packages were distributed continually to all under-five children in the puskesmas that experienced the increase of the cases for a month in average. Additionally, puskesmas did not optimally involve village staffs and sub district office staffs in the PMT-P program activities. The implementation of PMT- P in puskesmas that experienced the decrease of undernourished cases is better. Accurate determination of the target and improvement of community involvement should be able to decrease undernourished cases.